The diaphanous gene of Drosophila interacts antagonistically with multiple wing hairs and plays a key role in wing hair morphogenesis. - Qiuheng Lu; Paul N Adler (PLoS ONE)
The Drosophila wing is covered by an array of distally pointing hairs that has served as a key model system for studying planar cell polarity (PCP). The adult cuticular hairs are formed in the pupae from cell extensions that contain extensive actin filaments and microtubules. The importance of the actin cytoskeleton for hair growth and morphogenesis is clear from the wide range of phenotypes seen in mutations in well-known actin regulators. Formin proteins promote the formation of long actin filaments of the sort thought to be important for hair growth. We report here that the formin encoding diaphanous (dia) gene plays a key role in hair morphogenesis. Both loss of function mutations and the expression of a constitutively active Dia led to cells forming both morphologically abnormal hairs and multiple hairs. The conserved frizzled (fz)/starry night (stan) PCP pathway functions to restrict hair initiation and activation of the cytoskeleton to the distal most part of wing cells. It also ensures the formation of a single hair per cell. Our data suggest that the localized inhibition of Dia activity may be part of this mechanism. We found the expression of constitutively active Dia greatly expands the region for activation of the cytoskeleton and that dia functions antagonistically with multiple wing hairs (mwh), the most downstream member of the fz/stan pathway. Further we established that purified fragments of Dia and Mwh could be co-immunoprecipitated suggesting the genetic interaction could reflect a direct physical interaction.